Medals and degrees: factors influencing dual career of elite student athletes at the University of Debrecen - Lenténé Puskás, Andrea; Perényi, Szilvia (Applied Studies in Agribusiness and Commerce, 2015)
Career planning and goal setting play a significant role in the life of elite athletes gaining critical relevance during the overlapping years with university studies. As athletic career contain a necessary end and cannot serve as a profession for life, all athletes shall go through modification period in their professional lives. The athletic career shall come to an end and elite athletes need to find another profession for which they need to prepare as well. The specialities of this undertake is that the peak or the progressive cycle of athletic career often times overlap in time with high school and university studies. This definitely challenges those young athletes who made the decision to continue their studies at the university level beside their athletic careers. The objective of this study is to explore the main factors influencing the simultaneous realisation of studies and elite sport careers during university years. Part of a complex research approach on dual career in sport this study is aimed to gain information about methods of athletes for managing their dual tasks, the perceived relationship of student athletes to their peers, teachers and coaches, and their position on the relevant policy regulations provided by the university environment. Following the development of research instruments, data collection was conducted by focus-group interviews at the University of Debrecen among student elite athletes receiving sport scholarships (N=15). Level of success in sport, sport type (individual and team) and gender distribution was taking into account. The results shall contribute to the development of a future research instrument in a form of a questionnaire to assess aspects of dual career of athletes in case of larger samples. JEL code: Z20